2018
DOI: 10.1177/2377960818785155
|View full text |Cite
|
Sign up to set email alerts
|

The Burden Experience of Formal and Informal Caregivers of Older Adults With Hip Fracture in Nigeria

Abstract: Introduction: The incidence of hip fracture among older adults in Nigeria is on the rise. As a result, there is increased frequency of hospitalization, patient suffering, family burden, and societal cost. One dimension that has not been sufficiently explored is the burden of care experienced by informal and formal caregivers. Objectives: To describe the care burden experience of informal and formal caregivers for older adults with hip fractures in a specialized orthopedic center in Nigeria and to explore in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 34 publications
2
17
0
2
Order By: Relevance
“…Family caregivers in this study described the recovery of hip‐fractured persons with cognitive impairment as slow as dripping water. Our findings are supported by prior reports that older hip‐fractured persons’ cognitive function influenced family caregivers’ role in providing instrumental and supervisory care at home and made caring difficult for family caregivers (Diameta et al, 2018; Ramazanu & Griffiths, 2017). Our study also adds to the knowledge base by identifying family caregivers’ experiences in providing care to hip‐fractured older persons with cognitive impairment during a slow recovery process, implementing strategies, and related contextual factors.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Family caregivers in this study described the recovery of hip‐fractured persons with cognitive impairment as slow as dripping water. Our findings are supported by prior reports that older hip‐fractured persons’ cognitive function influenced family caregivers’ role in providing instrumental and supervisory care at home and made caring difficult for family caregivers (Diameta et al, 2018; Ramazanu & Griffiths, 2017). Our study also adds to the knowledge base by identifying family caregivers’ experiences in providing care to hip‐fractured older persons with cognitive impairment during a slow recovery process, implementing strategies, and related contextual factors.…”
Section: Discussionsupporting
confidence: 90%
“…The cognitive function of older hip‐fractured persons was found to influence family caregivers’ role in providing instrumental and supervisory care at home and made care difficult for family caregivers (Diameta et al, 2018; Ramazanu & Griffiths, 2017). However, few studies were found on family caregiving processes for hip‐fractured persons with cognitive impairment.…”
mentioning
confidence: 99%
“…In developed countries, many studies have been conducted among the older adults and their caregivers to examine prevalence and health effects of caregivers’ burden as well as coping and support strategies ( Herrera, Lee, Nanyonjo, Laufman, & Torres-Vigil, 2009 ; Schulz & Martire, 2004 ). Previous studies in the sub-Saharan ( Dotchin et al, 2014 and Mugisha et al, 2013 ) as well Nigerian studies on caregiving have focused on specific illness conditions especially mental illness ( Adeosun, 2013 and Jack‐Ide, Uys, & Middleton, 2013 ) and ( Yusuf, Nuhu, & Akinbiyi, 2009 ) older adults with hip fracture ( Diameta et al, 2018 ), cancer ( Akpan-Idiok & Anarado, 2014 ), and patients with End-Stage Renal Disease ( Oyegbile & Brysiewicz, 2017 ). Similarly, Faronbi (2018) and Faronbi and Olaogun (2017) quantitatively examined the burden of caregiving for older adults chronic illness.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Worldwide, the estimated number of hip fractures in older adults is expected to reach 6.3 million in 2050. 3 While there is no national directory that reports the incidence of hip fracture among older adults in Nigeria, there are 1 McMaster University, Canada 2 Emerging Researchers & Professionals in Ageing-African Network, Nigeria 3 University of Portharcourt Teaching Hospital, Nigeria 4 Mackenzie Physiotherapy Clinic, Nigeria 5 Obafemi Awolowo Teaching Hospital Complex, Nigeria 6 Cedacrest Hopitals, Nigeria 7 Lily Hospitals Limited, Nigeria 8 Western University, Canada 9 University of Nigeria, Nigeria 10 Humanity Hospital Limited, Nigeria 11 University of Manitoba, Canada 12 Peak Wellness Center, Abuja 13 Federal Medical Center, Nigeria 14 Elroi Mission Hospital, Nigeria 15 Glasgow Caledonian University, UK individual studies that have explored the incidence of hip fracture among older adults in different regions in Nigeria. For instance, Adebajo et al 4 reported a 2.1 per 100,000 and 2.0 per 100,000 incidents in hip fractures in men and women older than 50 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since 98.6% of Nigerians pay out of pocket for most healthcare services including physiotherapy, 8 patients/relatives have reported a financial burden as a result of caring for older adults with hip fracture. 9 Mobility deficits in older adults with hip fractures are often missed during hospital-to-home transitions. [10][11][12] Additionally, studies have reported that functional deficits such as gait, speed, muscle strength or reduced activities in daily living after discharge are independent functional predictors for hospital readmission for older adults.…”
Section: Introductionmentioning
confidence: 99%